Stabilisasi Tanah Gambut Dengan Kapur Terhadap Nilai California Beraring Ratio (CBR) - Muthia Anggraini; Mitra Sari; Fadrizal Lubis (Universitas Teuku Umar, 2021)
The sontang-duri cross road is a causeway that is often traversed by large trucks. The problem that occurs is that the road construction has been destroyed, because this road has a subgrade of peat, where peat soil is considered to be less profitable soil if used as the basis of a road construction. Peat soil has low soil bearing capacity, high water content and high compressibility. The purpose of this study was to determine the percentage value of the California Bearing Ratio (CBR) peat soil stabilized using lime using variations of 5%, 10%, and 15%. The method used for this problem is to carry out chemical stabilization with the mixture of lime. From the results of the tests that have been carried out, the original soil CBR value of 95% maximum dry density was obtained at 1.40%. The addition of lime to peat soil with variations of 5%, 10%, and 15% increased the CBR value. The increase that reaches the requirements to be used as a road subgrade is in the variation of 15%, with a CBR value of 8%. The requirement to be used as a road subgrade is based on the bina marga specification of 6% so it can be concluded that the addition of lime for peat soil stabilization can increase the CBR value.